Produção de sentidos e representações da mulher na campanha A linda ex de o Boticário - Santos, Janaina Alves Pereira Almeida dos (2019)
The present work is the result of research carried out at the Discourse and Ontology Study Group - GEDON, at the Federal University of Alagoas. The research arose from the interest to analyze how the discursive practices used by television advertising reached the public and which ideologies exist in this type of persuasive communication. Thus, we seek to know the advertising of the brand O Boticário, having as analytical corpus the campaign A Linda Ex, broadcasted in 2016 on Brazilian free TV, with the purpose of considering how to build the senses about women, family and marriage, in the discourse of the cosmetics brand, and how the effects of meaning arising from slips in this discourse reinforce the current representations of women in society. For that, we use as theoretical and conceptual basis the French Discourse Analysis (AD), based on the knowledge produced from Michel Pêcheux. This choice is justified since AD is configured as a field of confluence between Linguistics and Social Sciences, which presupposes the non-neutrality of saying, the non-transparency of language and its commitment to the senses and ideology. . In addition to Pêcheux, we seek to anchor our research on authors who have made it possible to establish the dialogue between AD and Advertising, from a critical and analytical perspective, namely: Eni Orlandi, Lukács, Courtine, Indursky, Grigoletto, among others. This reference made it possible to verify that the discourse about the beauty of women gains strength as a support axis for the more explicit purpose of the brand, which is to sell its cosmetic products. However, and as a way to ensure the sale of its products, the brand draws on the social imagination of divorced woman, making the campaign target audience believe that everything is a matter of beauty. Thus, the advertising piece, which is constantly interspersed with interdiscourses, endorses the demand on women to assume a historical and socially determined role in maintaining the monogamous family in the context of capitalist and androcentric society. In this sense, it reinforces the socially produced stereotypes about the subject position wife / mother, responsible for raising children and caring for the family (husband).